Meaning predictability in word formation : novel, context-free naming units - Štekauer, Pavol (Studies in functional and structural linguistics ;, 2005)
This book aims to contribute to a growing interest amongst psycholinguists and morphologists in the mechanisms of meaning predictability. It presents a brand-new model of the meaning-prediction of novel, context-free naming units, relating the wordformation and wordinterpretation processes. Unlike previous studies, mostly focussed on N+N compounds, the scope of this book is much wider. It not only covers all types of complex words, but also discusses a whole range of predictability-boosting and -reducing conditions. Two measures are introduced, the Predictability Rate and the Objectified Predictability Rate, in order to compare the strength of predictable readings both within a word and relative to the most predictable readings of other coinages. Four extensive experiments indicate inter alia the equal predicting capacity of native and non-native speakers, the close interconnection between linguistic and extra-linguistic factors, the important role of prototypical semes, and the usual dominance of a single central reading.